TINJAUAN YURIDIS MENGENAI PRINSIP ITIKAD BAIK DALAM PENOLAKAN KLAIM ASURANSI JIWA KREDIT - Millania Tri Rahmadhani; Novina Sri Indiraharti (Fakultas Hukum Universitas Trisakti, 2022)
Because of a breach of the concept of good faith (Utmost Good Faith), which is governed by article 251 of the Indonesian Commercial Code, insurance claims for life insurance are frequently denied by the insurer. The matter is stated as follows: What are the legal remedies for credit life insurance that is not paid by PT Cigna Insurance? The application of descriptive normative research methodologies, the qualitative processing of secondary data, and the deductive drawing of conclusions. The findings of the study, the discussion, and the conclusion that PT. Cigna Insurance's decision to deny credit life insurance claims was modified by article 251 of the Criminal Code led to the discovery that the reasons for the decision were made to the fact that RR. L. Nuning Lestari M is the late Alm. Agoes Soegiarto's successor was brought about by a breach of the covenant of good faith between RR. L. Nuning Lestari M and Alm. Agoes Soegiarto.